Model Pembelajaran Kolaboratif : Tinjauan Literatur - Tina Suryani Siregar; Anike Renti Anita Sinaga; Apri Ananta Sitio; Icha Netanya Sianturi; Rajo Hasim Lubis (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study aims to analyze the application of collaborative learning models in the digital era based on a literature review of 15 related journals. Collaborative learning, which involves social interaction between learners and utilization of digital technology, has great potential in improving student engagement, concept understanding, and 21st century skills. The analysis shows that technology-based collaborative learning, such as the use of Learning Management Systems (LMS), online platforms and other collaborative applications, is effective in improving learning quality. However, the implementation of this model also faces challenges related to technology access, digital literacy, and online learning management. In conclusion, collaborative learning model in the digital era can enrich learners' learning experience, provided it is supported by adequate infrastructure and training for educators. Technology-based collaborative learning has the potential to be a solution to create a more inclusive, interactive and competency-based education in the future.